Augmented Reality Integrated Poster as a Media to Introduce Gauss Science Figure and The Concept of Electric Field - Salma Afifah (Journal of Teaching and Learning Physics, 2023)
Poster is one of the learning media used by educators and students in the learning process. However, poster that only displayed in two-dimensional form makes the poster unable to describe three-dimensional concepts in physics, so it requires a combination with augmented reality technology that can combine two- and three-dimensional objects. Therefore, this study aims to produce an integrated augmented reality poster as a medium to introduce the scientist Johann Carl Friedrich Gauss or known as Gauss and the concept of the electric field. This research was developed using the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The results of the feasibility tests have been carried out by material experts, media experts, and users and it can be concluded that the integrated augmented reality poster as a medium to introduce scientist Gauss and the concept of the electric field is feasible to be used as a teaching media in learning physics.